Efektifitas Konseling Kelompok Untuk Meningkatkan Kepercayaan Diri Siswa - Samsaifil Samsafil; Edison; Aprilia (Jurnal Multidisipliner Bharasumba, 2026)
This study aimed to determine the effectiveness of group counseling services in improving the self-confidence of eighth-grade students at SMP Negeri 17 Baubau. The study employed a pre-experimental method using a one-group pretest–posttest design. The participants consisted of 10 students selected based on their low levels of self-confidence. Data were collected using a self-confidence scale administered before and after the implementation of the group counseling program. The data were analyzed using the Wilcoxon Signed Rank Test to examine differences between the pretest and posttest scores. The results showed an Asymp. Sig. (2-tailed) value of 0.005, which was lower than the significance level of 0.05 (0.005 < 0.05), indicating a significant difference between the pretest and posttest scores. Therefore, the alternative hypothesis was accepted, demonstrating that group counseling services were effective in enhancing students' self-confidence and supporting their social and psychological development.